Methylene Blue Application to Lessen Pain: Its Analgesic Effect and Mechanism - Lee, Seung Won; Han, Hee Chul (Frontiers in Neuroscience, 2021)
Methylene blue (MB) is a cationic thiazine dye, widely used as a biological stain and chemical indicator. Growing evidence have revealed that MB functions to restore abnormal vasodilation and notably it is implicated even in pain relief. Physicians began to inject MB into degenerated discs to relieve pain in patients with chronic discogenic low back pain (CDLBP), and some of them achieved remarkable outcomes. For osteoarthritis and colitis, MB abates inflammation by suppressing nitric oxide production, and ultimately relieves pain. However, despite this clinical efficacy, MB have not attracted much public attention in terms of pain relief. Accordingly, this review focuses on how MB lessens pain, noting three major actions of this dye: anti-inflammation, sodium current reduction, and denervation. Moreover, we showed controversies over the efficacy of MB on CDLBP and raised also toxicity issues to look into the limitation of MB application. This analysis is the first attempt to illustrate its analgesic effects, which may offer a novel insight into MB as a pain-relief dye.